Principles of Rorschach interpretation - Weiner, Irving B. (LEA series in personality and clinical psychology., 2003)
This second edition of Irving Weiner's comprehensive, clinician-friendly guide to utilizing the Rorschach for personality description has been revised to reflect both modifications in the Rorschach Comprehensive System and new evidence concerning the soundness and utility of Rorschach assessment.